A method for micro-nanoscale ceramic preparation based on additive manufacturing hydrogel precursor

By combining additive manufacturing of hydrogel precursors with multi-stage precision sintering processes, the problems of powder agglomeration and process complexity in micro-nano-scale ceramic manufacturing have been solved, enabling the preparation of high-density, fine-grained micro-nano-structured ceramics and improving the mechanical properties and structural integrity of the ceramics.

CN123026432APending Publication Date: 2026-11-03HUAZHONG UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611333425.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-31
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing methods for manufacturing micro- and nano-scale ceramics suffer from problems such as powder agglomeration, complex processes, and limited material selection, making it difficult to achieve the preparation of high-density, fine-grained ceramics.

Method used

A method combining additive manufacturing of hydrogel precursors with multi-stage precision sintering is used to prepare micro-nano-scale ceramics through shape fabrication and material selection phase separation, including hydrogel template wetting and multi-stage precision sintering processes.

Benefits of technology

This method enables the fabrication of micro/nano-structured ceramics with high degree of freedom, high fidelity, and fine grains, reducing the damage to the ceramic structure caused by moisture evaporation, gel oxidation, and thermal stress, and improving mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123026432A_ABST
    Figure CN123026432A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of inorganic non-metallic material preparation, and more particularly relates to a micro-nano scale ceramic preparation method based on an additive manufacturing hydrogel precursor. The method comprises additive manufacturing of a hydrogel precursor, precursor solution infiltration, and multi-stage precision sintering. The multi-stage sintering comprises a dehydration stage, a degreasing stage, a carbon removal stage, a preliminary densification stage, a final densification stage, and a slow cooling stage. Through the strategy of'shape manufacturing and material selection separation', the carbon pollution is completely removed through the heat preservation in the carbon removal stage, low-temperature densification is achieved in the temperature interval where the grain boundary diffusion is active and the grain boundary migration is inhibited through multi-stage precision sintering, and finally, the micro-nano scale ceramic with high fidelity, high density, small grain size and completely removed carbon pollution is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application belongs to the field of inorganic non-metallic material preparation technology, and more specifically, relates to a method for preparing micro / nano-scale ceramics based on additive manufacturing of hydrogel precursors. In particular, it relates to a method for preparing high-density, fine-grained micro / nano-scale ceramics by combining additive manufacturing of hydrogel precursors with precursor solution wetting, coupled with a multi-stage precision sintering process. Background Technology

[0002] Oxide and composite oxide ceramic materials (alumina, zirconium oxide, titanium oxide, barium titanate, potassium sodium niobate, etc.) are widely used in aerospace, microelectromechanical systems (MEMS), bio-implants, and catalyst supports due to their excellent high-temperature resistance, mechanical strength, wear resistance, and corrosion resistance. With the development of micro-nano manufacturing technology, ceramics with complex micro-nano structures have shown great application potential in fields such as mechanical metamaterials, microfluidic chips, and high-temperature sensors.

[0003] Currently, common manufacturing methods for micro / nano-scale ceramics mainly include: 3D printing based on ceramic powder, anodic template method, and sol-gel method combined with template method. For example, CN117106287A discloses an ultrafast laser-induced micro / nano particle jetting 3D printing method for hierarchical porous ceramics, including: S1, three-dimensional model design and model slicing of the hierarchical lattice ceramic structure; S2, ultrafast laser-induced fine jetting to form a single-layer structure with precise deposition patterns; S3, layer-by-layer deposition to form a hierarchical lattice ceramic deposit green body, accompanied by external field control during the deposition process; S4, Joule flash firing of the hierarchical lattice ceramic, with auxiliary thermal control and auxiliary magnetic field external force control during the firing process; S5, preparation and shaping of the precision hierarchical lattice ceramic. The above existing technologies require the use of micro / nano-scale ceramic powder as raw material, and inevitably encounter phenomena such as powder agglomeration during the manufacturing process, which affects the mechanical properties of the final product. They also have shortcomings such as complex processes and limited material selection. Summary of the Invention

[0004] To address the shortcomings of existing technologies, this application aims to provide a method for preparing micro / nano-scale ceramics based on additive manufacturing of hydrogel precursors. By adopting a strategy of "separation of shape manufacturing and material selection" and combining a multi-stage precision sintering process, the method achieves controllable preparation of high-density, fine-grained micro / nano-scale ceramics, thereby solving the technical problems of powder agglomeration, complex processes, and limited material selection in existing micro / nano-scale ceramic manufacturing methods.

[0005] This invention provides a method for preparing micro-nano-scale ceramics based on additive manufacturing of hydrogel precursors, mainly to achieve the following objectives: 1. To achieve micro-nano-scale ceramic preparation; 2. To achieve low-temperature sintering of ceramics to refine ceramic grains; 3. To achieve high-fidelity ceramic manufacturing with complex three-dimensional structures; 4. To improve the mechanical strength and structural integrity of ceramic microstructures.

[0006] To achieve the above objectives, in a first aspect, this application provides a method for preparing micro / nano-scale ceramics based on additive manufacturing of hydrogel precursors, comprising the following steps: S1: Prepare hydrogel templates with pre-defined three-dimensional micro / nano structures using additive manufacturing processes; S2: Immerse the hydrogel template obtained in step S1 into a precursor solution containing metal ions, allow it to stand and wet, and then dry it; the metal ions include the metal ions corresponding to the target ceramic material. S3: The sample dried in step S2 is subjected to multi-stage precision sintering under a flowing atmosphere to obtain micro-nano-scale ceramics. The multi-stage precision sintering includes a dehydration stage, a degreasing stage, a decarburization stage, a primary densification stage, a final densification stage, and a slow cooling stage.

[0007] Preferably, the micro / nano-scale ceramic has a characteristic size of 10-500 μm for its three-dimensional micro / nano structure.

[0008] Preferably, the hydrogel is made of one or more of polyethylene glycol diacrylate, sodium alginate-polyvinyl alcohol, methacrylamide gelatin, polyvinyl alcohol, and chitosan.

[0009] Preferably, the ceramic is an oxide ceramic.

[0010] More preferably, the oxide ceramic is one or more of alumina, zirconium oxide, titanium oxide, barium titanate, and potassium sodium niobate.

[0011] Preferably, the additive manufacturing process in step S1 is a stereolithography process, a digital light processing process, or an ink direct writing process.

[0012] Preferably, the metal ion precursor solution in step S2 is selected from aqueous solutions of one or more of the following soluble metal salts: chlorides, nitrates, acetates, sulfates, alkoxides, or organometallic complexes.

[0013] More preferably, the metal ions in step S2 also include metal ions corresponding to the sintering aid, wherein the sintering aid is one or more of magnesium chloride, magnesium nitrate, manganese nitrate, lanthanum nitrate, and yttrium chloride, and the mass percentage of the sintering aid in the precursor solution containing metal ions is 0.5-2.0 wt%.

[0014] Preferably, the temperature for static soaking in step S2 is 50~65℃, and the soaking time is 24~48h.

[0015] More preferably, the multi-stage precision sintering in step S3 includes: Dehydration stage: Increase the temperature from room temperature to 90-110℃ at a rate of 0.5-1.5℃ / min, and hold for 40-60 minutes; Degreasing stage: Heat to 220~280℃ at a heating rate of 0.5~1.5℃ / min, and hold for 120~180min; Decarbonization stage: Heat to 520~580℃ at a heating rate of 0.5~1.5℃ / min, and hold for 150~200min; Primary densification stage: The temperature is increased to the grain boundary migration temperature T1 of the ceramic material at a heating rate of 1.5~2.5℃ / min, and held for 90~120min; Final densification stage: Cooling at a rate of 2.5~3.5℃ / min to below the grain boundary migration temperature T1 and above the grain boundary diffusion temperature T2, inhibiting grain boundary migration and promoting grain boundary diffusion, and holding at this temperature for 1200~1500min; Slow cooling stage: The temperature is reduced to 700-800℃ at a cooling rate of 0.5~1.5℃ / min, and then air-cooled to room temperature along with the furnace.

[0016] Compared with existing technologies, the technical solutions conceived in this application combine a "separation of shape manufacturing and material selection" strategy with a multi-stage precision sintering process. The use of hydrogel precursors significantly improves the freedom and precision of shape selection, while the multi-stage precision sintering process greatly reduces the damage to the ceramic structure caused by moisture evaporation, gel oxidation, thermal stress, and phase transformation stress, and generates fine ceramic grains that significantly improve the mechanical properties of the ceramic. Together, these two processes achieve high-freedom, high-fidelity, and fine-grained micro / nano-scale ceramic manufacturing. Overall, the technical solutions conceived in this application have the following beneficial effects compared with existing technologies: (1) High fidelity: The expected hydrogel precursor is obtained through additive manufacturing process, and the occurrence of cracks, deformation and other phenomena is reduced through a carefully designed multi-stage precision sintering process, resulting in micro-nano structure ceramics with high fidelity.

[0017] (2) Low temperature sintering: Through multi-stage precision sintering process design, after phase transformation and preliminary sintering are completed at T1 temperature, the temperature is rapidly reduced to below T1 temperature and kept at above T2 temperature for a long time. This temperature is in the range where grain boundary diffusion is active and grain boundary migration is suppressed. High density can be achieved without significant grain growth, and fine grain strengthening effect can be obtained.

[0018] (3) Avoid thermal stress damage: The multi-stage sintering process effectively controls and releases thermal stress by slowly heating up and controlling the temperature down in a programmed manner.

[0019] (4) The process is highly versatile: This process is applicable to most metal oxide ceramics, and only the precursor solution needs to be changed. Attached Figure Description

[0020] Figure 1 This is a flowchart of the method for preparing micro / nano-structured ceramics provided in the embodiments of this application; Figure 2 These are images of the hydrogel precursor and ceramic sample provided in the embodiments of this application; Figure 3 This is an XRD pattern of a sintered sample provided in an embodiment of this application.

[0021] Figure 4 This is a photograph of the sample obtained by sintering in Comparative Example 2 of this application. Detailed Implementation

[0022] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.

[0023] This application discloses a method for manufacturing micro-nano-scale ceramics. This method combines hydrogel precursors with multi-stage precision sintering, effectively solving common problems in existing manufacturing methods such as powder agglomeration, complex processes, and grain coarsening. It proposes a technical strategy of "separation of shape manufacturing and material selection" to prepare micro-nano-structured ceramics with high degree of freedom, high fidelity, and fine grains.

[0024] When preparing micro / nano-structured ceramics using the method of this invention, the growing ceramic structure is extremely fragile due to the large stresses caused by hydrogel dehydration stress, gel oxidation stress, phase transformation stress, and grain growth stress. If these stresses are not released or suppressed, the ceramic may fail to form properly, resulting in an incomplete structure. This invention, through a carefully designed multi-stage precision sintering process, includes dehydration, debinding, decarburization, primary densification, and final densification stages, while simultaneously controlling a low temperature change rate. This effectively releases various stresses during the sintering process and successfully solves the problem of difficult ceramic structure formation.

[0025] This application discloses a method for preparing micro / nano-scale ceramics based on additive manufacturing of hydrogel precursors, aiming to produce micro / nano-scale ceramics with high degree of freedom, high fidelity, and fine grains. Figure 1 As shown, the method includes the following steps: S1: Select a suitable hydrogel and preparation method to prepare a hydrogel precursor with a pre-defined three-dimensional micro / nano structure. This hydrogel material should have a large porosity to facilitate ion exchange with the precursor solution. In this embodiment, the hydrogel materials that can be selected are: polyethylene glycol diacrylate (PEGDA), sodium alginate-polyvinyl alcohol, methacrylamide gelatin (GelMA), polyvinyl alcohol (PVA), chitosan, etc. The preparation method can be additive manufacturing processes such as: stereolithography (SLA), digital light processing (DLP), direct ink writing (DIW), etc. S2: Immerse the hydrogel precursor obtained in S1 into a precursor solution containing metal ions and allow it to stand and soak at a certain temperature. In this embodiment, the metal ion precursor solution is selected from aqueous solutions of one or more of the following soluble metal salts: chlorides, nitrates, acetates, sulfates, alkoxides, or organometallic complexes.

[0026] Furthermore, the precursor solution also needs to contain 0.5-2.0 wt% of a sintering aid, which can be one or more of magnesium chloride, magnesium nitrate, manganese nitrate, lanthanum nitrate, yttrium chloride, etc. The sintering aid can help lower the sintering temperature, promote the formation of fine ceramic grains, and improve the mechanical properties of the ceramic.

[0027] S3: The sample after S2 and drying is sintered in a flowing atmosphere in multiple stages, including dehydration stage, degreasing stage, decarburization stage, primary densification stage, final densification stage and slow cooling stage.

[0028] The micro / nano-scale ceramic fabrication method of this invention is applicable to the fabrication of arbitrary three-dimensional micro / nano-structured ceramics. Typical configurations encompassing three-dimensional micro / nano-structures include, but are not limited to, lattice framework structures, curved surface structures, and porous structures with random or gradient pores; these three types of configurations overlap geometrically. The dimensions of the most basic unit or key geometric details constituting the above-mentioned micro / nano-structures, i.e., the structural feature dimensions of the three-dimensional micro / nano-scale ceramics, are 10-500 μm.

[0029] In this invention, the three-dimensional micro / nano structure of the hydrogel template is designed based on the structure of the target ceramic and adapted to the corresponding additive manufacturing process. Experimental results show that the ceramic body prepared by the method of this invention has a volume shrinkage rate of approximately 60% compared to the original template (commonly 55%~65%). Accordingly, in practical operation, the template size can be proportionally enlarged by 1.55~1.65 times according to the micro / nano structure size of the target ceramic, thereby determining the final size of the hydrogel template.

[0030] The preparation method of this invention is applicable to the preparation of various ceramic materials, including but not limited to oxide ceramics. In some embodiments, the oxide ceramic is alumina (Al2O3), zirconium oxide (ZrO2), titanium oxide (TiO2), etc., or composite oxides such as barium titanate (BaTiO3), potassium sodium niobate (KNN), etc.

[0031] In some embodiments, the temperature for static soaking in step S2 is 50~65°C, and the soaking time is 24~48h.

[0032] The multi-stage precision sintering process in step S3 of this invention includes sequentially raising the temperature to the evaporation temperature, degreasing temperature, and purification temperature at a relatively slow and controllable rate, holding each temperature for a certain time, then raising the temperature to the grain boundary migration temperature T1 at a controllable rate, holding it for a short time, and then lowering the temperature to below the grain boundary migration temperature T1 and above the grain boundary diffusion temperature T2 at a controllable rate to suppress grain boundary migration and promote grain boundary diffusion. After holding the temperature for a period of time, the temperature is continuously cooled to room temperature to complete the sintering.

[0033] In some embodiments, the multi-stage sintering process sequentially includes: a dehydration stage, in which the temperature is raised to about 100°C at a slow rate and held for a period of time to allow water in the hydrogel to escape fully without damaging the precursor structure, while metal ions undergo hydrolysis; a degreasing stage, in which the temperature is raised to the degreasing temperature at a slow rate and held for a period of time to allow the hydrogel to decompose fully; a decarburization stage, in which the temperature is raised to about 550°C at a slow rate and held for a period of time to fully remove residual carbon between grain boundaries; a primary densification stage, in which the temperature is raised to the grain boundary migration temperature T1 at a slow rate to allow metal oxides to migrate to grain boundaries and grains to grow; a final densification stage, in which the temperature is lowered at a certain rate to below the grain boundary migration temperature T1 and above the grain boundary diffusion temperature T2 to inhibit grain boundary migration, promote grain boundary diffusion, and held for a period of time to allow the ceramic to achieve complete densification; and a slow cooling stage, in which the temperature is lowered to 800°C at a controllable rate and then air-cooled in the furnace to alleviate the damage of thermal stress to the structure.

[0034] In a preferred embodiment, the multi-stage precision sintering in step S3 includes: Dehydration stage: Increase the temperature from room temperature to 90-110℃ at a rate of 0.5-1.5℃ / min, and hold for 40-60 minutes; Degreasing stage: Heat to 220~280℃ at a heating rate of 0.5~1.5℃ / min, and hold for 120~180min; Decarbonization stage: Heat to 520~580℃ at a heating rate of 0.5~1.5℃ / min, and hold for 150~200min; Primary densification stage: The temperature is increased to the grain boundary migration temperature T1 of the ceramic material at a heating rate of 1.5~2.5℃ / min, and held for 90~120min; Final densification stage: Cooling at a rate of 2.5~3.5℃ / min to below the grain boundary migration temperature T1 and above the grain boundary diffusion temperature T2, inhibiting grain boundary migration and promoting grain boundary diffusion, and holding at this temperature for 1200~1500min. Slow cooling stage: The temperature is reduced to 700-800℃ at a cooling rate of 0.5~1.5℃ / min, and then air-cooled to room temperature along with the furnace.

[0035] The T1 and T2 temperatures vary for different ceramic materials. For example, the grain boundary migration temperature (T1) of alumina (Al2O3) ceramics is 1400-1600℃, and the grain boundary diffusion temperature (T2) is 1000-1200℃; the grain boundary migration temperature (T1) of zirconia (ZrO2) ceramics is 1200-1500℃, and the grain boundary diffusion temperature (T2) is 900-1100℃; the grain boundary migration temperature (T1) of titanium oxide (TiO2) ceramics is 900-1100℃, and the grain boundary diffusion temperature (T2) is 700-900℃; the grain boundary migration temperature (T1) of barium titanate (BaTiO3) ceramics is 1100-1300℃, and the grain boundary diffusion temperature (T2) is 900-1050℃; and the grain boundary migration temperature (T1) of potassium sodium niobate (KNN) ceramics is 1000-1100℃, and the grain boundary diffusion temperature (T2) is 850-950℃.

[0036] The micro / nano-scale ceramics prepared using the method described in this application achieve phase separation between shape fabrication and material selection by using hydrogels, which are easier to form and offer greater freedom in shape selection, as shape templates, combined with a metal ion-containing precursor solution as the material supply. Furthermore, multi-stage precision sintering significantly reduces the damage to the ceramic structure caused by moisture evaporation, gel oxidation, thermal stress, and phase transformation stress, while generating fine ceramic grains that greatly improve the mechanical properties of the ceramics. This results in the preparation of micro / nano-scale ceramics with high degree of freedom, high fidelity, and fine grains. This application overcomes the challenges in preparing micro / nano-scale ceramics through a strategy of "phase separation between shape fabrication and material selection" combined with a multi-stage precision sintering process.

[0037] The present invention proposes a method for preparing micro / nano-scale ceramics based on additive manufacturing of hydrogel precursors, comprising: additive manufacturing of hydrogel precursors, precursor solution wetting, and multi-stage precision sintering. The multi-stage sintering includes a dehydration stage, a degreasing stage, a decarburization stage, a primary densification stage, a final densification stage, and a slow cooling stage. This invention employs a strategy of "separation of shape manufacturing and material selection," thoroughly removing carbon contamination through heat preservation in the decarburization stage, and achieving low-temperature densification in a temperature range where grain boundary diffusion is active and grain boundary migration is suppressed through multi-stage precision sintering. This ultimately yields micro / nano-scale ceramics with high fidelity, high density, fine grains, and complete removal of carbon contamination. The method of this invention is process-controllable and highly versatile, with broad application prospects in microelectromechanical systems, mechanical metamaterials, and biomedical devices.

[0038] The embodiments of the present invention are implemented under the premise of the technical solution of the present invention, and detailed implementation methods and processes are given. However, the protection scope of the present invention is not limited to the following embodiments. The process parameters in the following embodiments that do not specify specific conditions are generally in accordance with conventional conditions.

[0039] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.

[0040] Example 1 1. Preparation of hydrogel slurry: Components: Polyethylene glycol diacrylate (PEGDA, average molecular weight 600, containing ≤ppm MEHQ stabilizer), carboxymethyl cellulose (CMC), lithium phenyl (2,4,6-trimethylbenzoyl)phosphine (LAP), tartrazine, deionized water; Formula: PEGDA 15g, CMC 0.3g, LAP 0.2g, Tartrazine 0.05g, Deionized Water 35g; Steps: Stir magnetically (500 rpm) until homogeneous.

[0041] 2. A hydrogel template with a TPMS structure was fabricated using digital light processing (DLP) technology: Substrate printing: Layer 1: UV power 5 mW / cm², exposure 30 s, layer thickness 25 μm; Layer 2: UV power 5 mW / cm², exposure 15 s, layer thickness 25 μm; Scaffold printing: Layers 1-5: UV power 20 mW / cm², exposure 30 s; Layers 6-10: UV power 15 mW / cm², exposure 25 s; Remaining layers: UV power 13 mW / cm², exposure 16 s; Post-treatment: Rinse the uncured slurry with deionized water and store it moist.

[0042] 3. Preparation of aluminum chloride solution: Components: Aluminum chloride hexahydrate (AlCl3) 6H2O), deionized water, magnesium chloride (MgCl2); Ratio: AlCl3 60.36g of 6H2O, 73g of deionized water, and 0.24g of MgCl2; Steps: Stir magnetically (500 rpm) until homogeneous.

[0043] 4. Ion exchange: The printed hydrogel template was placed in an aluminum chloride (2.5 mol / L) solution and immersed at 65°C for 48 hours. After immersion, it was dried to constant weight.

[0044] 5. Multi-stage sintering: The samples were placed in a box furnace for multi-stage sintering. Dehydration stage: Increase the temperature from room temperature to 100℃ at a rate of 1℃ / min and hold for 60min; Degreasing stage: Increase the temperature from 100℃ to 250℃ at a rate of 1℃ / min, and hold for 150min; Decarbonization stage: The temperature is increased from 250℃ to 550℃ at a rate of 1℃ / min, and held for 180min. Primary densification stage: The temperature is increased from 550℃ to T1=1400℃ at a heating rate of 2℃ / min (the grain boundary migration temperature T1 of alumina Al2O3 ceramic is 1400-1600℃), and held for 100min. Final densification stage: The temperature was reduced from 1400℃ to 1300℃ at a cooling rate of 3℃ / min (the grain boundary diffusion temperature T2 of alumina Al2O3 ceramic is 1000-1200℃), and held for 1200min. Cooling stage: The temperature is reduced from 1300℃ to 800℃ at a cooling rate of 1℃ / min, and then air-cooled to room temperature along with the furnace.

[0045] The sintered sample was white and had a complete structure. SEM observation showed that the grains were fine equiaxed crystals with an average grain size of 1.2 μm and a relative density of 97.3%. XRD showed that it was pure α-Al2O3.

[0046] Figure 2 The images show the hydrogel precursor and the prepared ceramic sample from Example 1. It can be seen that the sintering shrinkage of the hydrogel is about 60%, and the ceramics before and after sintering have a TPMS structure, good shape retention, and no defects such as deformation or warping.

[0047] Figure 3 The image shows the XRD pattern of the sintered alumina sample. It can be seen that the alumina ceramic prepared by this method is pure and is α-Al2O3, proving that the hydrogel components were completely removed and no impurities remained.

[0048] Example 2 Steps 1 and 2 are the same as in Example 1; 3. Precursor solution infiltration: A 2.0 mol / L aqueous solution of zirconium oxychloride (ZrOCl2·8H2O) was prepared, and 3 mol% yttrium chloride (YCl3) was added as a stabilizer and sintering aid. The hydrogel template was immersed in the solution and allowed to stand at 65°C for 48 hours.

[0049] 4. Multi-stage sintering: The dehydration, degreasing, and decarbonization stages are the same as in Example 1.

[0050] Primary densification stage: The temperature is increased from 550℃ to T1=1300℃ at a heating rate of 2℃ / min (the grain boundary migration temperature T1 of zirconia ZrO2 ceramic is 1200-1500℃), and held for 90min. Final densification stage: The temperature was reduced from 1300℃ to 1195℃ at a cooling rate of 3℃ / min (the grain boundary diffusion temperature T2 of zirconia ZrO2 ceramic is 900-1100℃), and held for 1200min. Cooling stage: Same as in Example 1.

[0051] The sintered sample was white and had a complete structure. SEM observation showed that the grains were fine equiaxed crystals with an average grain size of 0.6 μm and a relative density of 95.8%. XRD showed that it was tetragonal zirconium oxide.

[0052] Example 3 Steps 1 and 2 are the same as in Example 1; 3. Precursor solution infiltration: Prepare a water-ethanol mixed solution (volume ratio 1:1) containing 0.2 mol / L barium acetate (Ba(CH3COO)2) and 0.2 mol / L tetrabutyl titanate (Ti(OC4H9)4), and add a small amount of acetic acid to adjust the pH to 3-4 to prevent hydrolysis and precipitation. Immerse the hydrogel precursor in this solution and allow it to stand at 55°C for 48 hours.

[0053] 4. Multi-stage sintering: The dehydration, degreasing, and decarbonization stages are the same as in Example 1.

[0054] Primary densification stage: The temperature is increased from 550℃ to T1=1300℃ at a heating rate of 2℃ / min (the grain boundary migration temperature T1 of barium titanate BaTiO3 ceramic is 1100-1300℃), and held for 90min. Final densification stage: The temperature was reduced from 1300℃ to T2=1095℃ at a cooling rate of 3℃ / min (the grain boundary diffusion temperature T2 of barium titanate BaTiO3 ceramic is 900-1050℃), and held for 1200min. Cooling stage: Same as in Example 1.

[0055] The sintered sample was white and had a complete structure. SEM observation showed that the grains were fine equiaxed crystals with an average grain size of 1.1 μm and a relative density of 93.1%. XRD showed that it was barium titanate.

[0056] Comparative Example 1 Steps 1 and 2 are the same as in Example 1; 3. Precursor solution infiltration: The printed hydrogel precursor was placed in an aluminum chloride (1.0 mol / L) solution and soaked at 65°C for 48 h. After soaking, it was dried to constant weight.

[0057] Step 4 is the same as in Example 1.

[0058] The sintered sample was white and could not maintain a complete structure. SEM showed that the grain size was approximately 1 μm.

[0059] Comparative Example 2 Steps 1, 2, and 3 are the same as in Example 1.

[0060] 4. One-step sintering The temperature was increased directly from room temperature to 1500℃ at a rate of 5℃ / min, held for 4 hours, and then allowed to cool naturally.

[0061] Results: The sample could not maintain a complete structure; the grains were coarse (>5μm), such as... Figure 4 As shown.

[0062] Comparative Example 3 The other steps are the same as in Example 1, except that no dehydration stage is set in the multi-stage sintering, and the temperature is directly raised from room temperature to the degreasing temperature.

[0063] Result: The sample was directly crushed into powder and could not maintain its intact structure.

[0064] Comparative Example 4 The other steps are the same as in Example 1, except that no decarburization stage is set in the multi-stage sintering. After degreasing, the temperature is directly raised to cause phase transformation and primary densification.

[0065] Results: Although the sample retained its intact structure, its mechanical properties were extremely poor, and even the application of a very small external force would damage its structure.

[0066] Comparative Example 1, lacking sintering aids, may have resulted in an inability to obtain a well-formed ceramic with a complete structure due to the high sintering temperature of alumina. Comparative Examples 2 to 4 illustrate that the multi-stage sintering control process of this invention is indispensable and requires synergistic cooperation to effectively release various stresses during sintering and prevent stress concentration from damaging the ceramic structure; otherwise, only a result like... Figure 4 The fragmented ceramics shown cannot be used to obtain micro / nano-structured ceramics with complete structures.

[0067] It should be understood that expressions such as "comprising" and "may include" as used in this application indicate the existence of the disclosed functions, operations, or constituent elements, and do not limit one or more additional functions, operations, and constituent elements. In this application, terms such as "comprising" and / or "having" may be interpreted as indicating a specific characteristic, number, operation, constituent element, component, or combination thereof, but should not be interpreted as excluding the existence or possibility of adding one or more other characteristics, numbers, operations, constituent elements, components, or combinations thereof.

[0068] It should be understood that the terms “center,” “upper,” “lower,” “front,” “rear,” “left,” “right,” “vertical,” “horizontal,” “inner,” “outer,” “clockwise,” “counterclockwise,” “axial,” “radial,” and “circumferential” indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are used only for the convenience of describing this application and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on this application.

[0069] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this application, "multiple" means two or more, unless otherwise explicitly specified.

[0070] In this application, unless otherwise expressly specified and limited, the terms "installation," "connection," "linking," and "fixing," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection between two components. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances.

[0071] The above description is merely a specific embodiment of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A method for preparing micro / nano-scale ceramics based on additive manufacturing of hydrogel precursors, characterized in that, Includes the following steps: S1: Prepare hydrogel templates with pre-defined three-dimensional micro / nano structures using additive manufacturing processes; S2: Immerse the hydrogel template obtained in step S1 into a precursor solution containing metal ions, allow it to stand and wet, and then dry it; the metal ions include the metal ions corresponding to the target ceramic material. S3: The sample dried in step S2 is subjected to multi-stage precision sintering under a flowing atmosphere to obtain micro-nano-scale ceramics. The multi-stage precision sintering includes a dehydration stage, a degreasing stage, a decarburization stage, a primary densification stage, a final densification stage, and a slow cooling stage.

2. The preparation method according to claim 1, characterized in that, The micro-nano-scale ceramics have a characteristic size of 10-500 μm for their three-dimensional micro-nano structures.

3. The preparation method according to claim 1, characterized in that, The hydrogel is made of one or more of the following materials: polyethylene glycol diacrylate, sodium alginate-polyvinyl alcohol, methacrylamide gelatin, polyvinyl alcohol, and chitosan.

4. The preparation method according to claim 1, characterized in that, The ceramic is an oxide ceramic.

5. The preparation method according to claim 3, characterized in that, The oxide ceramic is one or more of alumina, zirconium oxide, titanium oxide, barium titanate, and potassium sodium niobate.

6. The preparation method according to claim 1, characterized in that, The additive manufacturing process mentioned in step S1 is stereolithography, digital light processing, or ink direct writing.

7. The preparation method according to claim 1, characterized in that, The metal ion precursor solution mentioned in step S2 is selected from aqueous solutions of one or more of the following soluble metal salts: chlorides, nitrates, acetates, sulfates, alkoxides, or organometallic complexes.

8. The preparation method according to claim 1, characterized in that, The metal ions mentioned in step S2 also include metal ions corresponding to sintering aids. The sintering aids are one or more of magnesium chloride, magnesium nitrate, manganese nitrate, lanthanum nitrate, and yttrium chloride. The mass percentage of the sintering aids in the precursor solution containing metal ions is 0.5-2.0 wt%.

9. The preparation method according to claim 1, characterized in that, The temperature for static soaking in step S2 is 50~65℃, and the soaking time is 24~48h.

10. The preparation method according to claim 1, characterized in that, The multi-stage precision sintering described in step S3 includes: Dehydration stage: Increase the temperature from room temperature to 90-110℃ at a rate of 0.5-1.5℃ / min, and hold for 40-60 minutes; Degreasing stage: Heat to 220~280℃ at a heating rate of 0.5~1.5℃ / min, and hold for 120~180min; Decarbonization stage: Heat to 520~580℃ at a heating rate of 0.5~1.5℃ / min, and hold for 150~200min; Primary densification stage: The temperature is increased to the grain boundary migration temperature T1 of the ceramic material at a heating rate of 1.5~2.5℃ / min, and held for 90~120min; Final densification stage: Cooling at a rate of 2.5~3.5℃ / min to below the grain boundary migration temperature T1 and above the grain boundary diffusion temperature T2, inhibiting grain boundary migration and promoting grain boundary diffusion, and holding at this temperature for 1200~1500min; Slow cooling stage: The temperature is reduced to 700-800℃ at a cooling rate of 0.5~1.5℃ / min, and then air-cooled to room temperature along with the furnace.

Citation Information

Patent Citations

  • Efficient ceramic epoxy resin composite material and preparation method thereof

    CN117106287A